A Novel Learning Multi-Swarm Particle Swarm Optimization - Borowska, Bożena (Wydawnictwo Politechniki Łódzkiej, 2023)
Particle swarm optimization (PSO) is one of the metaheuristic optimization methods. Because of its many advantages, it is often used to solve real-world engineering problems. However, in case of complex, multidimensional tasks, PSO faces some problems related to premature convergence and stagnation in local optima. To eliminate this inconveniences, in this paper, a new learning multi-swarm particle swarm optimization method (LMPSO) with local search operator has been proposed. The presented approach was tested on a set of nonlinear functions and a CEC2015 test suite. The obtained results were compared with other optimization methods.
Keywords: learning particle swarm optimization; learning strategy; multiswarm; particle swarm optimization; pso; optimization; swarm intelligence; nauka optymalizacji roju cząstek; strategia uczenia się; optymalizacja roju cząstek; pso; optymalizacja; inteligencja roju